2021
DOI: 10.3390/chemosensors9070154
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configuration Sensing of Chiral Aryl- and Aryloxy-Propionic Acids by Biphenyl Chiroptical Probes

Abstract: The absolute configuration of chiral 2-aryl and 2-aryloxy propionic acids, which are among the most common chiral environmental pollutants, has been readily and reliably established by either electronic circular dichroism spectroscopy or optical rotation measurements employing suitably designed 4,4′-disubstituted biphenyl probes. In fact, the 4,4′-biphenyl substitution gives rise to a red shift of the diagnostic electronic circular dichroism signal of the biphenyl A band employed for the configuration assignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Dibenz[c,e]azepines constitute an important class of compounds widely employed as chiral or pro-chiral scaffolds for the construction of chiral catalysts for asymmetric synthesis or probes for chiral molecular recognition. In particular, 1,1 -binaphthylazepines have been widely employed as chiral ligands in organometallic catalysis [1][2][3][4][5] and organocatalysis [6][7][8][9][10], while not-atropisomerically stable (i.e., tropos) 1,1 -biphenylazepines have been reported both as structural motifs for the construction of the chiral ligands [9][10][11][12][13][14][15] and as the chiroptical probes for the absolute configuration assignment to the chiral acids [16][17][18][19] and amines [14,20]. In fact, in 1,1 -biphenylazepines the low phenyl-phenyl rotational barrier allows, at room temperature, a free interconversion of the two possible M and P atropisomeric forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dibenz[c,e]azepines constitute an important class of compounds widely employed as chiral or pro-chiral scaffolds for the construction of chiral catalysts for asymmetric synthesis or probes for chiral molecular recognition. In particular, 1,1 -binaphthylazepines have been widely employed as chiral ligands in organometallic catalysis [1][2][3][4][5] and organocatalysis [6][7][8][9][10], while not-atropisomerically stable (i.e., tropos) 1,1 -biphenylazepines have been reported both as structural motifs for the construction of the chiral ligands [9][10][11][12][13][14][15] and as the chiroptical probes for the absolute configuration assignment to the chiral acids [16][17][18][19] and amines [14,20]. In fact, in 1,1 -biphenylazepines the low phenyl-phenyl rotational barrier allows, at room temperature, a free interconversion of the two possible M and P atropisomeric forms.…”
Section: Introductionmentioning
confidence: 99%
“…This makes this molecular system a unique probe for detection of molecular chirality because, when this moiety is linked to a chiral compound, a centralto-axial chirality induction occurs and the stereogenic center(s) of the substrate induces a preferred biphenyl twist in the azepine, making this chiral itself. As reported above, this effect has been exploited to assemble chiral catalysts and reagents, joining the flexible biphenyl moiety to an atropisomerically stable binaphthyl moiety [10][11][12][13][14] or introducing one or two stereogenic centers on the benzylic positions [21,22], and to build chiroptical probes for the absolute configuration assignment to chiral acids [16][17][18][19] and amines [14,20]. In this latter application, the biphenylazepine moiety acts as a chirality sensor, assuming a preferred twist in dependence of the chiral substrate absolute configuration.…”
Section: Introductionmentioning
confidence: 99%
“…A particular family of binaphthyls is constituted by 1,1 -binaphthylazepines which, since the first example reported by Cram and Mazaleyrat in 1981 [6], have been widely employed both as chiral ligands in organometallic catalysis [7][8][9][10] and catalysts in organocatalysis [11]. Moreover, structurally similar tropos biphenylazepine analogues have been described both as structural motifs for the construction of chiral ligands [12] and as chiroptical probes for the absolute configuration assignment to chiral acids [13][14][15][16] and amines [12,17]. One of the most successful applications of 1,1 -binaphthylazepines in asymmetric catalysis have been reported by Maruoka and coworkers, who described the use of differently functionalized chiral binaphthylazepiniun ions in phase transfer catalysis for asymmetric alkylations, Michael additions, and aldol reactions [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although many chiroptical probes have been described so far, very few examples report their application to natural products of unknown AC [23,24]. Only very recently we have shown that 2,2 -bridged biphenyls, introduced by us some years ago for the AC assignment of chiral threo [25] and erythro [26] diols, carboxylic acids [27][28][29], and primary amines [30,31], also provide a versatile probe for the AC assignment of complex natural products [32,33]. In particular, we applied the biphenyl approach to assign AC to natural phytotoxins bearing a threo diol moiety [32] or a chiral acid group [33].…”
Section: Introductionmentioning
confidence: 99%